Nanodiamonds for advanced optical bioimaging and beyond. (February 2019) - Prabhakar, Neeraj; Rosenholm, Jessica M.
Abstract: Nanodiamond (ND) has emerged as an intriguing material in recent years both industrially and in research. During the last decade, ND has furthered its way into the biomedical field, mainly due to its inherent photoluminescent properties. In parallel, the development of advanced biomedical imaging methods and techniques has faced a steep upswing, making these two a 'perfect match'. The optical and physical properties of ND can be tuned, rendering them highly interesting as versatile biomedical imaging probes. In this short review, we will cover a few of the most recently emerged applications of NDs in biomedical imaging and contemplate on current challenges and future directions. Graphical abstract: Image 1